Modeling a Standard Loop-Mediated Isothermal Amplification Reaction and Its Modification Involving Additional Inner Primers - Liana U. Akhmetzianova; Constantin I. Mikhaylenko; Dmitry A. Chemeris; Valery D. Khairitdinov; Assol R. Sakhabutdinova; Irek M. Gubaydullin; Ravil R. Garafutdinov; Alexey V. Chemeris (Biomolecules)
Loop-mediated isothermal amplification (LAMP) was developed a quarter of a century ago, but it is still not exactly clear how this reaction proceeds. Only a few articles have focused on the kinetics of LAMP and the types of products formed. In this work, 10 types were identified and named. A basic dumbbell structure, Z6_dmb(1), consists of six zones and triggers the LAMP cycle. Due to self-priming, Z6_dmb(1) transforms into hairpin structure Z9_hp(1) and then into linearized strand Z9_li(1), carrying also strand Z6_dmb(2). Through similar transformations, it again generates strand Z6_dmb(1), completing the first LAMP cycle and starting a new one. The next stage of the exponential phase starts from two Z15_hp hairpin structures generated in the LAMP cycle, which next turn into Z15_li → Z27_hp → Z27_li → Z51_hp → and so forth. Modeling of a new type of the reaction, namely, pseudo-hemi-nested LAMP (phn-LAMP), was carried out. phn-LAMP involves three inner primers: two forward (FIP and extraFIP) and one backward inner primer, or vice versa. phn-LAMP has an advantage over LAMP involving loop or stem primers and over MIP-LAMP (multiple inner primers).